2006
DOI: 10.4161/cc.5.10.2769
|View full text |Cite
|
Sign up to set email alerts
|

Bur1/Bur2 and the Ctk Complex in Yeast: The Split Personality of Mammalian P-TEFb

Abstract: Eukaryotic organisms possess a host of factors that regulate transcriptional elongation. In higher eukaryotes, the transcription factor P-TEFb not only regulates phosphorylation of the RNA polymerase II C-terminal domain, but it also inhibits the action of transcriptional repressors and is required for the association of several elongation factors with the transcribing polymerase. In the yeast Saccharomyces cerevisiae, the cyclin dependent kinases Bur1/Bur2 and Ctk complex (Ctk1, 2 and 3) are also able to impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 40 publications
7
64
0
Order By: Relevance
“…However, as previously discussed by Wood and Shilatifard, there are both important similarities and distinctions between the yeast and human P-TEFb complexes. 35 Our results expand upon the many studies in yeast and demonstrate important distinctions between yeast and mammals. We have shown that CDK9 not only regulates H3K36me3, which is a characteristic of the yeast CTD kinase Ctk1, but also controls H2Bub1 and H3K4me3 which is a function of Bur1 in yeast.…”
Section: Similarities and Distinctions Between P-tefb Function In Yeasupporting
confidence: 81%
“…However, as previously discussed by Wood and Shilatifard, there are both important similarities and distinctions between the yeast and human P-TEFb complexes. 35 Our results expand upon the many studies in yeast and demonstrate important distinctions between yeast and mammals. We have shown that CDK9 not only regulates H3K36me3, which is a characteristic of the yeast CTD kinase Ctk1, but also controls H2Bub1 and H3K4me3 which is a function of Bur1 in yeast.…”
Section: Similarities and Distinctions Between P-tefb Function In Yeasupporting
confidence: 81%
“…BUR kinase also phosphorylates Rad6, leading to the ubiquitination of histone H2B on K123 (31,51). Because K123 ubiquitination also has a positive effect on elongation by RNAPII (52), it could be that it is H2B ubiquitination rather than Spt5 CTR phosphorylation that helps overcome the inhibiting effects of Set2 and Rpd3S on elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The Bur complex implements CTD phosphorylation early in the transcription cycle, while the Ctk complex implements CTD phosphorylation during the elongation phase of RNA Pol II (9). CDK9 was long considered to be the only CTD Ser2 kinase in metazoans, but recently the Drosophila dCdk12/dCyclin K complex was shown to be the major CTD Ser2 kinase implementing Ser2 phosphorylation during the elongation stage, analogous to the S. cerevisiae Ctk1/2 complex (10).…”
mentioning
confidence: 99%